Analysis of a Finite Quantum Well - Khan, Imran (Journal of Electrical Engineering, 2012)
In this paper one dimensional (1D) quantum confinement in a Finite Quantum Well (FQW) is analyzed through a simulator using MATLAB. A particle behavior inside a FQW is discussed and analyzed. The effect of various parameters such as well boundary thickness, depth of the well and width of the well are discussed. The results are compared with the Infinite Quantum Well (IQW). Different types of potential structures behavior can be analyzed by using this simulator which is very useful before fabrication. Journal of Electrical Engineering The Institution of Engineers, Bangladesh Vol. EE 37, No. II, December, 2011